2020
DOI: 10.1177/0263775820959677
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating office space: Digital technologies and the platformization of work

Abstract: Digital technologies enable the dispersal of office work from physical office buildings. The same technologies involve a counter tendency of concentration where offices are shared by different businesses, often for short periods, via the ‘space as service’ model. These opposing tendencies of workspace dispersal and concentration indicate the contingencies of technologies of work, in which their operations are mutually shaped by workplaces. Understanding what a technology of work is requires examining its situa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 66 publications
0
35
0
2
Order By: Relevance
“…In previous research, they have been identified as nodal points for numerous work-related trends, including work precarization, virtualization, and flexibilization (De Peuter and Cohen, 2015;Leclercq-Vandelannoitte and Isaac, 2016). Richardson (2020) appropriately recognizes the coworking space as a flexible "space of services" which-akin to the model flexible worker herself-is always modifiable.…”
Section: Disconnective Workplace Designsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous research, they have been identified as nodal points for numerous work-related trends, including work precarization, virtualization, and flexibilization (De Peuter and Cohen, 2015;Leclercq-Vandelannoitte and Isaac, 2016). Richardson (2020) appropriately recognizes the coworking space as a flexible "space of services" which-akin to the model flexible worker herself-is always modifiable.…”
Section: Disconnective Workplace Designsmentioning
confidence: 99%
“…Technologies of work-such as calendars, video conference software, laptops, Slack, etc.-are reflections of contemporary (Silicon Valley-ingrained) work norms and shape how we work (Wajcman, 2019a(Wajcman, , 2019b. Richardson (2020) notes in regards to connective technologies of work that they tend "less to divide space according to a specific function, and more to create spaces of coordination that can adjust the definition of purposeful activity" (p. 349). Such technologies, and the escalating platformization of work especially, she argues, do "not necessarily fix location" (p. 359) but rather stimulates de-territorialization.…”
Section: Disconnective Technologies Of Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Many city governments have displayed an ambivalence toward attracting tech firms, particularly over regulatory norms relating to the likes of Uber and Airbnb (McNeill, 2016). The struggles of platform 'gig' workers have been explored in several ways: Uber drivers by Pollio (2019) and Wells et al (2020); Deliveroo by Richardson (2020a). A significant amount of work has charted the impact of Silicon Valley platforms on urban life in the growing South, as seen in Pollio's (2019Pollio's ( , 2021 studies of Uber drivers in Cape Town and Mumbai, and Bedi's (2016) ethnography of how different taxi business models 'land' and are adapted to local laws and norms.…”
Section: Apps Platforms and Citiesmentioning
confidence: 99%
“…Information about customers provided by the Internet enables e-commerce to create personalized and individual-oriented products. Digital platforms have become a new phenomenon; today they are one of the key components of global economic exchange, creating new market mechanisms (Richardson, 2020). Enterprises often have a presence on social media, but their website remains the primary focus where customers inform, communicate, and buy their products or services (Kim et al, 2018).…”
Section: Enterprise Digital Dividementioning
confidence: 99%